STUDIES ON VARIABILITY IN TWO COLLETOTRICHUM SPECIES CAUSING ANTHRACNOSE AND FRUIT ROT OF CHILLIES IN PUNJAB - J. S. JHOOTY, T. S. THIND AND (Indian Phytopathology, 2002)
A marked variation in the symptoms caused by Colietotrichum capsici and C. g[oeosporoides causing anthracnose of chillies was observed. Based on lesion type and morphological characters, more than 150 isolates of these species obtained from different chilli growing areas in Punjab were grouped into 8 distinct categories (5 for C. capsici and 3 for C. g[oeosporoides). There existed a significant difference in the pathogenic behaviour of different types of isolates. Variation in response to mancozeb and captafol was more pronouced among isolate categories of C. capsici while isolates of C. g[oeosporoides did not show much difference. The study indicates the prevalence of different strains of these fungi in the State.